2020
DOI: 10.1111/are.14976
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density in Colossoma macropomum larviculture, a freshwater fish, in recirculating aquaculture system

Abstract: This study aimed to investigate stocking density during larviculture of Colossoma macropomum in recirculating aquaculture system with slightly saline water. Densities of 10 (D10), 30 (D30) and 50 (D50) larvae/L were tested with five replicates each. Larvae were fed with Artemia nauplii during the first 15 days and with commercial diet from day 16 to day 30. Water was maintained at a salinity of 2.01 ± 0.41 g of salt/L, and performance and survival were evaluated throughout the experiment. At the end of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 54 publications
(73 reference statements)
3
13
0
10
Order By: Relevance
“…Salinized water as a strategy for increase stocking density in Heros severus larviculture, an Amazonian ornamental fish Larviculture is considered the most important and critical stage of aquaculture production chain, once it is the phase of higher animal fragility (Evangelista et al, 2020;Reis et al, 2021;Santos et al, 2021). The larvae are sensitive to several stressful factors such as pathogenic infections, productive managements and changes in water parameters, which can lead to high mortality rates and reduce productivity (Zuanon et al, 2011;Dias et al, 2016;Abe et al, 2019).…”
Section: /8mentioning
confidence: 99%
See 2 more Smart Citations
“…Salinized water as a strategy for increase stocking density in Heros severus larviculture, an Amazonian ornamental fish Larviculture is considered the most important and critical stage of aquaculture production chain, once it is the phase of higher animal fragility (Evangelista et al, 2020;Reis et al, 2021;Santos et al, 2021). The larvae are sensitive to several stressful factors such as pathogenic infections, productive managements and changes in water parameters, which can lead to high mortality rates and reduce productivity (Zuanon et al, 2011;Dias et al, 2016;Abe et al, 2019).…”
Section: /8mentioning
confidence: 99%
“…Thus, the success of larviculture is determined by the optimal culture conditions, aiming to guarantee the adequate fish development (Dias et al, 2016;Campelo et al, 2019a;Abe et al, 2021). In this scenario, the effects of salinized water and stocking density of fish are some of the factors that should be studied, since they can directly affect the larviculture management (Luz et al, 2012;Dias et al, 2016;Santos et al, 2021).…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation
“…Larval stages are more sensitive to stocking densities compared to later stages of the fish life cycle. Previous studies have shown increased cannibalism, reduced feed intake, and poor growth performance among larvae of several fish species reared under high stocking densities (de Barros et al, 2019;Santos et al, 2020;Slembrouck et al, 2009;Sukumaran et al, 2011). Furthermore, manipulation of rearing conditions such as feeding regimes, feed composition, water salinity, and light spectrum among others could influence changes in the recommended optimal stocking densities required for the species' survival and performance.…”
mentioning
confidence: 99%
“…Santos et al (2020) investigated the influence of different stocking densities (10, 30, and 50 larvae/L) on the survival and growth performance of C. macropomum larvae reared in slightly saline RAS for 30 days. The authors recommended that larvae of C. macropomum can be successfully reared in slightly saline RAS at stocking densities of up to 50 larvae/L.In another study, de Souza e Silva et al (2021) found better survival, growth, and stress resistance in C. macropomum juveniles (initial weight 0.35 ± 0.10 g) at stocking densities of between 3 and 5 animals/L.…”
mentioning
confidence: 99%